On the come up [videorecording (DVD)] - Thomas, Angie; Lathan, Sanaa; Oyegun, Kay; Gray, Jamila C.; Randolph, Da'vine Joy, 1986-; Lil Yachty, 1997-; Method Man; Epps, Mike; Makin, Titus, Jr., 1989-; Rapsody, 1983-; Rapsody, 1983-; Lady London; et al. (Paramount, 2023)
Brianna Jackson is a sixteen-year-old gifted rapper who attempts to take the battle rap scene by storm to lift her family and do right by the legacy of her father a local hip-hop legend whose career was cut short by gang violence. But when her first hit song goes viral for all the wrong reasons, she finds herself torn between the authenticity that got her this far and the false persona that the industry wants to impose upon her. Based on the New York Times #1 best-selling novel by Angie Thomas.